Phenomenological Study of Factors Causing Pre-Marriage Pregnancy among Adolescents - Ailsya Regita Ardiningrum; Fatma Mesrawati; Firhan Surya Pradiafta; Faizil Hakim; Gilang Saputra Fajar; Resti Angreini (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
Youth is a period of transition from childhood to adulthood, at this time they are looking for identity and quite a lot of them express it with negative things. One of them is free sex which results in pregnancy out of marriage. Based on data from the statistical center, the number of adolescent promiscuity is currently increasing, the West Sumatra Regional Office (Kanwil) of the Ministry of Religion (Kemenag) noted, in 2021 the dispensation of early marriage. Whereas the previous year, only 786 women. This study aims to analyze how the factors that influence the occurrence of pregnancy out of marriage, such as level of education, economic conditions, social environment, educational background of parents, and lack of firmness from parents in educating their children. This research uses the method of a qualitative approach to phenomenology. Sources of data were taken from three informants through interviews who were selected using a purposive sampling technique. All interview results were analyzed using techniques Analysis interactive model Milles & Huberman. Research Findings show that five factors cause pregnancy out of marriage experienced by informants. These five factors are: i) the impact of dating, ii) lack of enthusiasm from parents to motivate their children to continue their studies, iii) lack of attention from the family, iv) letting children hang out too much without paying attention, v) feeling lazy from myself to continue to the high school level. Research result This can be used as information for the community to be able to find solutions to existing problems.